Strategi Pengembangan Ekspor Biji Kopi Sangrai Produksi UMKM di Jawa Timur - Nila Amelia Aji; Sumainah Fauziah (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
The development of exports of roasted coffee beans produced by MSMEs in East Java has declined due to the low efficiency of coffee cultivation in East Java. This study intends to identify the apprenticeship sector as a potential and limitation of roasted coffee bean exporters, identify external aspects of the sector as possibilities and risks for roasted coffee bean exporters, and interpret policies that can be implemented by MSMEs that are suitable for the conditions of the roasted coffee bean export business. This research method applies the SWOT description for policy analysis to develop exports of roasted coffee beans produced by MSMEs in East Java. The conclusions of this study state that the internal aspects that are potential for roasted coffee exports are the physical condition and quality of the roasted coffee beans, the duration of the distribution of roasted coffee beans, the ability of exporters to reach importing countries. Weaknesses in the export of roasted coffee beans are the promotion of roasted coffee beans, the amount of capital owned by exporters, suggestions for quality certificates. External aspects that allow the export of roasted coffee beans include export licensing, loyal customers who consume coffee, crop failures that occur in intermediary countries that also export roasted coffee beans, the selling price of roasted coffee beans, the level of demand for roasted coffee beans abroad, and so on. -etc. Threats to the export of roasted coffee beans are regulation of export duties, the role of the government, state competitors who are also producers of roasted coffee beans, weather changes. Policy preferences for developing exports of roasted coffee beans include maintaining customer loyalty, using licenses to facilitate exporters' access to importing countries, increasing capital by maximizing agreements from loyal customers, maximizing promotions, maximizing the quality and quantity of roasted coffee beans, and maximizing collaboration with institutions. In this regard, the government has a role in strengthening the implementation of promotional activities and capital in supporting the availability of assistance.